If you know that as and around 0, then this is easy.
Can somebody please show me how one computes
If we assign it to the variable and then take the logarithm of both sides, we should make it more easier. But after using some log laws and simplifications, I end up with
Now, because of ln(x), we need to use L'Hôspitals Rule but that isn't getting me anywhere since ln(x) keeps showing up. Can somebody help?
lim –sinxlnx = lim( –cosxlnx –sinx/x) = +infinity -> y -> infinity. (x -> 0+).
As a matter of interest, if your going to use sinx app x, might as well do it at the beginning to find lim y = (2/x)^x and log y = xln2 – xlnx to get same result.
Not finding fault, just giving a different perspective.
Edit: As a matter of further interest:
lim (2/x)^x = lim (2^x) lim (1/x)^x = lim (1/x)^x